TINGKAT KERACUNAN DAN ENZIM CHOLINESTERASE PADA DARAH PETANI PADI TAHUN 2016 (Studi Kasus Di Daerah Kepuh Anyar, Kabupaten Mojokerto) - Sella Puspita; Ngadino .; Koerniasari . (Poltekkes Kemenkes Surabaya, 2017)
ABSTRACTPesticides poisoning can affect the activity of cholinesterase enzyme that breaks down acetylcholinecompound that plays role in transmitting signal or stimulus into muscle nerve cells adjacent to each other thatstimuli can stop.Factors which allow the poisoning is the absence of PPE when working and unstandardized dosage ofpesticides usage. Poisoning can occur through skin contact, inhalation or oral. The purpose of this study is todetermine blood cholinesterase enzyme working activities on rice farmer in Kepuh Anyar, Mojokerto 2016. Thisstudy is a descriptive study with cross sectional approach. Data collection was carried out through laboratoryresults.The result of this study shows that the majority of rice farmers in Kepuh Anyar village, Mojokerto usedcarbamate and peritroid pesticides. The average age of farmers was 40 years, working duration of ≤ 8 hours,years of 11-15, and had sufficient knowledge to categories of pesticides. However, most of the farmers‟cholinesterase enzyme experienced poisoning in mild and moderate poisoning level.Related agencies are suggested to conduct counseling about the dangers of pesticide contamination toagricultural sector. Further researchers are advised to analyze other factors that may affect the activity ofcholinesterase enzyme.Keywords : Work Activity of Cholinesterase Enzyme, rice farmers